Hot saline irrigation for haemostasis in functional endoscopic sinus surgery: a systematic review and meta-analysis. Issue 8 (25th August 2022) - Ranford, D; Fu, B; Surda, P; Rudd, J
Abstract: Objective: The aim of this study was to perform a systematic review and meta-analysis of existing evidence on the role of hot saline irrigation in patients undergoing functional endoscopic sinus surgery and its impact on the visibility of the surgical field. Method: A search of PubMed, Cochrane, Ovid databases and Google Scholar was performed. Results: Three randomised controlled trials were included. Pooled meta-analysis demonstrated a statistically significant better visibility of the surgical field, and a reduction in total blood loss and operating time during functional endoscopic sinus surgery in the hot saline irrigation group compared with the room temperature irrigation group. Subgroup analysis of studies that did not use vasoconstrictors showed a significant reduction in total blood loss and operating time. Conclusion: This is the first systematic review that addresses hot saline irrigation for haemostasis in functional endoscopic sinus surgery. The results suggest that hot saline irrigation in functional endoscopic sinus surgery for chronic rhinosinusitis may significantly improve visibility of the surgical field, reduce total blood loss by 20 per cent and decrease operating time by 9 minutes. However, there are limitations of the study because of the significant heterogeneity of the methods, quality and size of the studies.